2017
DOI: 10.5430/ijhe.v6n1p180
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Digital Story on Academic Achievement, Learning Motivation and Retention among University Students

Abstract: The aim of this study was to determine the effect of the learning environment where digital stories are used as a learning material on the motivation, academic success, retention, and and students' opinions. The study was carried out with mixed method which is a combination of quantitative and qualitative research approach. The study was implemented in Recep Tayyip Erdoğan University Education Faculty Turkish Education Department. Participants included 61 students, 31 in experimental group and 30 in control gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 20 publications
5
23
0
1
Order By: Relevance
“…A review of the literature has shown that there are some studies that corroborated with the findings of this research. In one of these studies, Aktaş and Uzuner Yurt (2017) concluded that Turkish pre-service teachers had difficulty in dubbing and creating stories while designing a digital story. The authors also found that digital storytelling contributed to motivations, and promoted permanent learning, technology use skills and writing skills.…”
Section: Discussionmentioning
confidence: 99%
“…A review of the literature has shown that there are some studies that corroborated with the findings of this research. In one of these studies, Aktaş and Uzuner Yurt (2017) concluded that Turkish pre-service teachers had difficulty in dubbing and creating stories while designing a digital story. The authors also found that digital storytelling contributed to motivations, and promoted permanent learning, technology use skills and writing skills.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that listening lessons made with DST positively affect learning and it is more effective than the listening lessons made by using voice records, it positively affects student motivation are reflected to research findings. Moreover, it is seen that DST develops listening skills both in creation process (Yuksel, Robin, & McNeil, 2011;Yang & Wu, 2012;Yoon, 2016;Aktas & Yurt, 2017) and as product output (Ramirez-Verdugo & Belmonte, 2007;(Abidin, Pour-Mohammadi, Souriyavongsa, Tiang, & Kim, 2011;Cigerci & Gultekin 2017) in the other studies conducted on listening.…”
Section: Discussionmentioning
confidence: 93%
“…Digital storytelling enhances a student engagement, in agreement with Akkerman, Admiraal, and Huizenga (2009) games had a positive effect on student engagement. Aktas and Yurt (2017) found that digital storytelling has a positive effect on permanent learning, too.…”
Section: Discussionmentioning
confidence: 98%